Youtube as a learning media for writing narrative text at SMP Muhammadiyah 1 Jambi - Yuni Fitriyani; Rasdawita; D, Yusra (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
Based on the observations of researchers during PLP at SMP Muhammadiyah 1 Jambi City, whenstudents read a narrative text in front of other students, then students do assignments according to the contents of the narrative text they are reading, but there are still students who do not understand the contents of the text, because the text is too long so students become unfocused. Therefore the researcher offers a learning media in the form of Youtube media that can be used by teachers in learning narrative text. The purpose of this researchto describe the use of YouTube as a learning medium for narrative text material in class VII SMP Muhammadiyah 1 Jambi City. The research was conducted at SMP Muhammadiyah 1 Jambi City, the subject of this research was a Class VII Indonesian teacher. The approach in this research is a qualitative approach. This type of research, descriptive. The data obtained is in the form of student work in using YouTube as a learning medium. The results showed that the use of YouTube as a learning medium for class VII narrative text material at SMP Muhammadiyah 1 Jambi City in its implementation was in accordance with the learning implementation plan. Starting from the teacher carrying out preliminary activities, then in the main stages the teacher explains, asks questions and determines the results of student work to be made, the teacher helps students determine themes, determines schedules for collecting work results, in closing activities the teacher concludes the learning that has been carried out.